Antimicrobial susceptibility pattern of enterococci isolated from various clinical samples in a tertiary care hospital in India - Sameena Khan; Hardik Bansal; Nageswari Gandham; Shahzad Mirza; Chanda Vyawahare; Rajashri Patil; Sahjid Mukhida; Nikunja Kumar Das (IMC Journal of Medical Science, 2023)
Background and objectives: Enterococci are significant human pathogens that are capable of causing various nosocomial infections. This study determined the antibiotic susceptibility pattern of enterococcal species isolated from various clinical specimens with special reference to vancomycin-resistant enterococci.